THE EFFECT OF ADDITION SILICA FUME, SUPERPLASTICIZER, AND BONDING TO REACHING HIGH QUALITY LIGHTWEIGHT CONCRETE - Ayuk Putri Yuliansari; Fredy Kurniawan (Neutron, 2019)
In this research, a lightweight concrete mixture was made with foam and made use of the remaining broken rock from the Crusher Machine process, which was washed ashes. Other added ingredients used in the mixture are Silica Fume, Superplasticizer (Admixture Type F) and Bonding. This reseach uses a mix design from Circular Letter Number: 44 / SE / M / 2015 Concerning Design Guidelines for Mixing Light Material with Foam Mortar for Road Construction, Ministry of PUPR. Trial mix variations carried out are in proportion (SF 5%; BO 0.5%), (SF 10%; BO 0.5%), (SF 5%; BO 1%), (SF 10%; BO 1% ), as well as foam agents with variations 1:20 and 1:40. The treatment process (curing) of the test object is immersed in a water bath, and the testing of the compressive strength of the test object is carried out at the age of 7 days, 14 days and 28 days. By using stone ash, lightweight concrete was obtained with an average specific gravity of 1722 kg / m3 to 1884 kg / m3. From the research results obtained the highest average compressive strength with the percentage of material that is in the variation of the SF 10% ; BO 0.5% and ratio foam (1) : water (40) only for K 190.6 kg/cm2 or FC 15.82 MPa. In each specimen the value of quality efficiency with the most optimum weight variation at SF 10% ; BO 0.5% with a coefficient value of 10.03%.